IMPLEMENTASI WAKAF PRODUKTIF DAN WAKAF TUNAI DI INDONESIA - Fitri Nur Latifah, S.E; Clarisa Eka Rismadayanti; Reyhan Septya Alamsyah; Lailatul Mukaromah; Tsurroya Putri Sa’adah (Universitas KH. A. Wahab Hasbullah, 2021)
Waqf here is giving some of the property to be used in a certain period that aims for a naivety or common interest. The purpose of this research is to seek information and knowledge about the implementation of productive waqf and cash waqf in Indonesia.Because of an implementation of waqf in this day and age is very minimal, therefore it is necessary to improve and understand for the community about it.The method used in the study is to use the literature review method, by collecting a number of articles, journals and others.Keywords: Waqf, productive waqf, Cash waqf